Cytotoxicity, antiviral and antimicrobial activities of alkaloids, flavonoids, and phenolic acids - KARTAL, MURAT; Ozcelik, Berrin; Kartal, MURAT; Orhan, Ilkay (My University, 2011)
Materials and methods: Antiviral activity of the compounds was tested against DNA virus herpes simplex type 1 and RNA virus parainfluenza (type-3). Cytotoxicity of the compounds was determined using Madin-Darby bovine kidney and Vero cell lines, and their cytopathogenic effects were expressed as maximum non-toxic concentration. Antibacterial activity was assayed against following bacteria and their isolated strains: Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae, Acinetobacter baumannii, Staphylococcus aureus, Enterococcus faecalis, and Bacillus subtilis, although they were screened by microdilution method against two fungi: Candida albicans and Candida parapsilosis.